ANALISIS INTENSITAS DAN LAMA PAPARAN KEBISINGAN DENGAN PENINGKATAN TEKANAN DARAH PADA KARYAWAN PERUSAHAAN MIGAS X DI JAMBI - Zainudin, Mokhamad; Harahap, Putri Sahara; Mirsiyanto, Eko (Scientific Of Environmental Health and Diseases, 2021)
ABSTRACT Noise is one of the physical hazards that is often found in the work environment, such as machines and tools that can be a source of noise. Noise has various kinds of effects on humans both physically and psychologically. One effect on the physiology is on the heart so that it can increase blood pressure. Using the Cross Sectional Survey method and total sampling in the second and third week of February 2020 with the location in the Oil and Gas Company X in Jambi. Respondents are workers who are in the CPS Area with age ≥ 20 years. The number of respondents was 60 (sixty people). From the results of the study found there were 51.7% with an increase in blood pressure, and 48.3% there was no increase in blood pressure. As many as 53.3% of workers were exposed to more than 85 dBA intensity, 46.7% with intensity ≤ 85 dBA. And as much as 58.3% of workers with a duration of exposure> 8 hours, and 41.7% of workers with a duration of exposure ≤ 8 hours. Chi Square statistical test can explain that there is a relationship between increased blood pressure with noise intensity and there is no significant relationship between duration of exposure with increased blood pressure. Thus it can be planned treatment to deal with the intensity of noise against workers both by optimizing the use of PPE as well as policies in regulating working hours of workers. In subsequent studies to pay more attention to risk factors that can be a confounding variable, and the selection of respondents that is more in line with the research is needed. Keywords: Noise, exposure duration, intensity, blood pressure ABSTRAK Kebisingan merupakan salah satu bahaya fisik yang sering dijumpai dalam lingkungan kerja, seperti mesin yang bisa menjadi sumber kebisingan. Kebisingan mempunyai berbagai macam efek kepada manusia baik secara fisik maupun psikologis. Salah satu efek terhadap fisiologis adalah terhadap jantung yaitu bisa meningkatkan tekanan darah. Dengan menggunakan metoda Survey Cross Sectional dan total sampling, Responden adalah pekerja yang berada di Area CPS dengan usia ≥ 20 tahun. Jumlah responden 60 (enam puluh) orang. Dari hasil penelitian didapatkan terdapat 51,7% dengan peningkatan tekanan darah, dan 48,3% tidak ada peningkatan tekanan darah. Sebanyak 53,3% pekerja terpapar lebih dari dengan intensitas > 85 dBA, 46,7% dengan intensitas ≤ 85 dBA. Serta sebanyak 58,3% pekerja dengan lama paparan > 8 Jam, dan 41,7% pekerja dengan lama paparan ≤ 8 Jam . Uji statistik Chi Square dapat menjelaskan bahwa ada hubungan antara peningkatan tekanan darah dengan intensitas kebisingan dan tidak ada hubungan yang signifikan antara lama paparan dengan peningkatan tekanan darah. Sehingga maka dapat direncanakan penanganan untuk menangani intensitas kebisingan terhadap pekerja baik dengan optimalisasi penggunaan APD maupun kebijakan-kebijakan dalam pengaturan jam kerja pekerja. Pada penelitian selanjutnya untuk lebih memperhatikan faktor-faktor resiko yang bisa menjadi variabel pengganggu, serta diperlukan pemilihan responden yang lebih sesuai dengan penelitian. Kata kunci : Kebisingan, lama paparan, intensitas, tekanan darah